2019
DOI: 10.1002/pros.23938
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum testosterone levels predict poor prognosis in castration‐resistant prostate cancer patients treated with docetaxel

Abstract: BackgroundThe role of testosterone as a prognostic factor for castration‐resistant prostate cancer treated with docetaxel in Japan was investigated.MethodsA total of 164 patients with castration‐resistant prostate cancer who received docetaxel treatment at Chiba University Hospital and an affiliated hospital were retrospectively analyzed. Testosterone and other clinical factors at the start of docetaxel treatment were evaluated with respect to overall survival and progression‐free survival.ResultsOf the 164 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…These studies showed that CRPC patients with suboptimal testosterone serum levels had significantly shorter progression-free survival following docetaxel treatment. 22,23 Our data strongly suggest that taxane efficacy can be optimised by maintaining suppression of testosterone levels in order to minimise interference with docetaxel tumour accumulation and block AR-driven prosurvival signalling. Several phase II/III trials are currently combining (novel) AR-targeted therapies with taxanes in mCRPC.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These studies showed that CRPC patients with suboptimal testosterone serum levels had significantly shorter progression-free survival following docetaxel treatment. 22,23 Our data strongly suggest that taxane efficacy can be optimised by maintaining suppression of testosterone levels in order to minimise interference with docetaxel tumour accumulation and block AR-driven prosurvival signalling. Several phase II/III trials are currently combining (novel) AR-targeted therapies with taxanes in mCRPC.…”
Section: Discussionmentioning
confidence: 86%
“…These studies showed that CRPC patients with suboptimal testosterone serum levels had significantly shorter progression-free survival following docetaxel treatment. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The high‐testosterone (TST) group had significantly shorter OS and PFS than the low‐TST group. Furthermore, a high serum TST predicted poor post‐docetaxel survival in patients who received subsequent therapy, including ARAT and/or cabazitaxel [ 44 ]. A serum testosterone level of 5 to < 50 ng/dl was a significant predictor for determining the efficacy of AR-targeted therapy [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“… 29 Higher serum TST values have been reported to be more responsive to novel ARAT, whereas lower TST values to be more responsive to docetaxel. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%